Implementasi politik luar negeri bebas aktif menjetang tahun 2000 - Soedarno, Soenarto (Kertas karya perorangan (TASKAP) ; pesenta kursus reguler., 1986)
Implementation of free and active foreign policy of Indonesia towards the year 2000; paper.